2021
DOI: 10.1016/j.celrep.2021.109707
|View full text |Cite
|
Sign up to set email alerts
|

ER exit sites in Drosophila display abundant ER-Golgi vesicles and pearled tubes but no megacarriers

Abstract: Highlights d Golgi in Drosophila contains a pre-cis-Golgi region equivalent to vertebrate ERGIC d COPII and COPI proteins localize to the center and periphery of ER exit sites, respectively d FIB-SEM imaging shows existence of vesicles consistent with COPI and COPII regular-sized vesicles d In addition to vesicles, FIB-SEM reveals short pearled tubes connecting ERES and Golgi

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 88 publications
3
39
0
Order By: Relevance
“…A recent manuscript studied the Drosophila ER-Golgi interface using SIM, APEX-TEM, and FIB-SEM. [45] Apart from unidentified 50 nm diameter vesicles in the drosophila cells that were absent from the mammalian system, [31] COPI and COPII localizations and proximity were compatible with the new model advocated here.…”
Section: Rough Edges Of the Copii Hypothesissupporting
confidence: 76%
“…A recent manuscript studied the Drosophila ER-Golgi interface using SIM, APEX-TEM, and FIB-SEM. [45] Apart from unidentified 50 nm diameter vesicles in the drosophila cells that were absent from the mammalian system, [31] COPI and COPII localizations and proximity were compatible with the new model advocated here.…”
Section: Rough Edges Of the Copii Hypothesissupporting
confidence: 76%
“…4F). These findings suggest that after residing in the tER or at ERES for approximately four minutes, the bulk of Serp-SBG translocates to an adjacent compartment, corresponding to Golgi cisternae (Yang et al, 2021), where the protein spends approximately eight minutes before exiting the Golgi apparatus (Fig. 4E).…”
Section: Resultsmentioning
confidence: 93%
“…S3A; Ivan et al, 2008) and localized adjacent to the cis -Golgi marker GRASP65-GFP (Fig. S3B; Yang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It would appear that COPII proteins play a novel role focussing on cargo selection rather than vesicle formation. On the other hand, it has recently been reported that ER exit sites (ERES) display abundant COPII vesicles and pearled tubes in Drosophila , similar to the tubular ERES extensions in mammalian cells [30,32]. These novel evidence of diverse ER exit routes may underpin the existence of flexible COPII carriers in eukaryotes.…”
Section: Copii Vesicles In Er Export: Conventional Identities With Di...mentioning
confidence: 99%